THE ROLE OF LEGAL ADDICTIVE SUBSTANCES IN SKIN PATHOLOGIES: A LITERATURE REVIEW - Marcin Durowicz; Sylwia Bartolik; Karolina Bieńkowska; Jan Drzymała; Iwona Górnicka; Anita Janda; Urszula Kierepka; Aleksandra Pastuszek; Radosław Pastuszek; Magdalena Rosiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective. The skin not only plays a fundamental role in protecting the body from external factors, but also participates in thermoregulatory, metabolic, immunological and sensory processes. More and more attention is being paid (both in the scientific community and among patients) to the impact of lifestyle, including the use of legal stimulants such as alcohol or products containing nicotine on the condition of the skin. The aim of this paper was to present the current state of knowledge regarding the impact of harmful, easily accessible and legal addictive substances on human skin and also to support an interdisciplinary approach to the prevention and treatment of skin pathologies associated with their use.Review methods. The research was conducted as a literature review based on information obtained from PubMed, Embase, GoogleScholar using combinations of the following keywords: skin, cigarettes, alcohol, nicotine, lifestyle, substance, abuse, cancer.The state of knowledge. Biological mechanisms through which alcohol and nicotine (in both traditional and e-cigarette forms) affect the condition of the skin include the induction of oxidative stress, microcirculation disturbances, modulation of the immune response and disruptions in collagen metabolism. These mechanisms influence wound healing, exacerbate the course of inflammatory skin diseases, contribute to the development of neoplastic lesions and accelerate the skin aging process. There are reports of potential therapeutic benefits of nicotine in certain dermatoses. However, researchers point out the methodological limitations in existing studies.Conclusion. Alcohol and tobacco products have a negative impact on the skin – they disrupt microcirculation, weaken the epidermal barrier, slow down wound healing and accelerate aging. In the context of the growing popularity of e-cigarettes and alternative forms of nicotine consumption, the need for further, well-designed research in this area is emphasized.